Cost-Benefit Analysis of Renewable Power under Full Subsidy Targeting Law Enforcement Conditions in Iran - Barimani, Mehdi (International Journal of Energy Economics and Policy, 2016)
Fossil energy extracted resources limitation, on the one hand and fossil energies induced environment pollution, on the other hand, have made renewable energies more attractive, especially for developing countries. Thus international programs and policies such as the UN programs have been considered in line with global sustainable development playing a special role for renewable energy resources. Although, in practice various factors in particular high initial cost and marginal price, not sufficient investment for localization and the associated technologies efficiency enhancement, taking external costs for granted in the economic equations and lack of supportive policies at local, regional and international levels have made renewable energies penetration and development very slow and limited. It is emphasized that rich fossil resources (standing 4th rank in oil reserves and 2nd in gas reserves) existence in Iran has been another giant obstacle for renewable energies development in Iran. Thus executing subsidy targeting policy and Article 44 of Iranian Constitutional law can be a great opportunity for renewable energies development in Iran. Through economically evaluating the renewable power and comparing it with fossil electricity under full subsidy targeting law enforcement conditions, renewable electricity marginal cost sensitivity analysis and various guaranteed renewable energies resources electricity purchase tariff proposal to the government , the researcher in this study hopes that the private sector investor ’s opportunity in this industry and subsequently, renewable electricity share increase in Iran energy basket will be provided. Keywords: Cost-Benefit Analysis; Sensitivity analysis; Renewable Power; Subsidy Targeting Law; COMFAR JEL Classifications: C87; H23; Q27; Q42